Hermeneutika Gadamer dan Aplikasinya terhadap Tafsir Ayat Pendidikan: (Gadamer's Hermeneutics and Its Application to the Interpretation of Educational Verses) - Nashihin, Muhammad; Wahyu Hidayati, Tri (STAI Ma'had Aly Al-Hikam Malang, 2025)
This article investigates the application of Hans-Georg Gadamer’s philosophical hermeneutics to Qur’anic verse Q.S. al-ʿAlaq:1, as interpreted in two contrasting commentaries: Tafsīr Jalālayn and Tafsīr al-Ibrīz. It asks how differing interpretive horizons shape educational meaning in Islamic exegesis. Positioning the study within philosophical Qur’anic hermeneutics, the analysis employs Gadamer’s key concepts—pre-understanding, fusion of horizons, and language as a medium of truth—to examine the textual and contextual layers of both tafsīrs. Jalālayn represents a classical, theological-legalist horizon, while al-Ibrīz embodies a Javanese pesantren-based cultural and spiritual horizon. The study finds that both commentaries reflect dynamic educational paradigms grounded in their respective historical and cultural contexts. It concludes that Gadamerian hermeneutics opens constructive avenues for dialogical, contextual Qur’anic interpretation and contributes to the development of culturally inclusive Islamic education. Artikel ini menelaah penerapan hermeneutika filosofis Hans-Georg Gadamer terhadap QS al-ʿAlaq:1 dalam Tafsīr Jalālayn dan Tafsīr al-Ibrīz. Pertanyaan utama yang diangkat adalah bagaimana perbedaan horizon penafsiran membentuk makna pendidikan dalam tafsir Al-Qur’an. Melalui pendekatan pre-understanding, fusion of horizons, dan bahasa sebagai medium kebenaran, ditemukan bahwa Jalālayn mewakili horizon klasik-teologis, sementara al-Ibrīz merefleksikan horizon budaya dan spiritual pesantren. Studi ini menyimpulkan bahwa pendekatan hermeneutika Gadamer menawarkan kontribusi penting dalam pengembangan tafsir Al-Qur’an yang dialogis dan kontekstual untuk pendidikan Islam